Muhammad Sinen's Political Communication Strategy In Maintaining Electability Towards The 2024 Simultaneous Regional Elections (case Study: Muhamad Sinen as Elected Mayor of Tidore City, North Maluku Province) - Masita Jainudin; Made Wilantara; Ajeng Iva Dwi Febriana (International journal of technology and education research, 2025)
The implementation of political communication strategies requires the need for the right approach so that political messages can be effectively accepted by the public, especially in areas with complex social, cultural, and political dynamics. This research aims to analyze the political communication strategies carried out by Muhammad Sinen in building an image, shaping public opinion, and strengthening political support in the City of Tidore Islands. The research method used is a qualitative approach with case studies, where data is obtained through in-depth interviews, observations, documentation, and literature review involving informants from various circles, including community leaders, success teams, and the general public. The results of the study show that the communication strategies used, such as face-to-face communication, the use of social media, social activities, and communication based on local wisdom, have proven to be effective in expanding the reach of political messages and strengthening closeness with the community. The obstacles faced include limited communication infrastructure, resistance from some groups, and local political dynamics that often change. The integration of local cultural values such as family, mutual cooperation, and respect for traditional leaders strengthens communication strategies so that they are more persuasive, inclusive, and able to build public trust. The findings of this study prove that the combination of modern communication media and local cultural values can increase the effectiveness of political communication strategies and strengthen the community's support base.